The Influence of Conversational AI on Consumer Behavior and Counterfactual Thinking: A Systematic Review - Bouhlal, Hind; Belahcen, Noureddine (European Scientific Journal, ESJ, 2025)
This document evaluates the development and importance of conversational AI, chatbots, and virtual assistants in human behavior and the process of making decisions. Designed to investigate the impact of AI on the personalization of user experiences, the study maps how the automation of decision-making and the alteration of cognitive processes like thinking in the counterfactual mode and regret are affected. The main idea is that while conversational AI service might improve the user experience and be more efficient, problems with transparency, personalization overdone and emotive manipulation might emerge. The conclusion of the research is that it is necessary to operate in a balanced way in order for the trust to be established, to be transparent, and to be authentic, thus reinforcing the transformative impact of conversational AI in e-commerce and consumer engagement in the future.